Implementing interventions to start HPV vaccination at age 9: Using the evidence we have - Heather M. Brandt; Alison Footman; Prajakta Adsul; Shoba Ramanadhan; Deanna Kepka (Taylor & Francis Group, 2023)
Human papillomavirus (HPV) vaccination is routinely recommended for adolescents aged 11 or 12 years but can begin at age 9. On-time HPV vaccination by the thirteenth birthday has proven to be effective in preventing HPV cancer and pre-cancer. However, HPV coverage rates continue to lag behind other routinely recommended vaccinations for adolescents. A promising approach to improving coverage is to start HPV vaccination at age 9. This approach has been endorsed by the American Academy of Pediatrics and the American Cancer Society. Benefits of this approach include increased time to complete vaccination series by the thirteenth birthday, additional spacing of recommended vaccines, and a more concentrated focus on cancer prevention messaging. While promising, little is known about how and if existing evidence-based interventions and approaches can be used to promote starting HPV vaccination at age 9. Implementation science frameworks offer scientific direction in how to adapt current and develop new interventions to promote starting HPV vaccination at age 9 and accelerate dissemination and prevent HPV cancers.